Research contribution and potential investigation on friction stir welding for AA2014 material family. (2021) - Swetha, S.; Padhy, Chinmaya Prasad
Abstract: Aluminum alloy 2014 has wide application. In its applications, aerospace and automobile industries are utilized well such Aluminum alloy. This article presents a novel approach of reviewing material related research to pave the path for new researchers. The aluminum is one of the popular materials and can be modified either to form a composite or augmenting the material properties with utilization of heat treatment methods. Friction stir welding is one of the advanced metals joining/ welding technology. This paper reviews how the two popular cases jointly contributing for creating mechanical structures. This papers covers parameter optimizations for friction stir welding of similar and dissimilar metals, mathematical modeling, post welding treatments, new tool contributions, grain structure effects, need for FSW and identified further research scope further research are consolidated and presented as research potential.